Unpacking the Taliban: A Hybrid of Delinquent Sanctimony - Qassem, Ahmad Shayeq (Politikologija religije, 2023)
Since its inception in 1994 as an organised group or network with a claim on rulership of the country, the Taliban has been generally described as an "Islamic movement" committed to the implementation of sharia in Afghanistan. Such description may accord well with the group’s professed objective but reveals itself reductive at best and misleading otherwise on closer scrutiny. This article argues that the "Taliban" represents a hybrid phenomenon that deploys religious and political narratives just as it deploys organised crime in pursuit of maximum power and profit.